Effects of whey products on performance of weaned pigs - Pope, S.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three trials were conducted utilizing 458 pigs with an average age of 21 days to study the effects of adding whole whey, or partially delactosed whey from two sources in the diet of weaned pigs on growth, feed intake, and feed efficiency. Additionally, the optimum length of time to feed whole whey and the relationship of age at weaning and addition of whey to the diet were studied. The addition of whey to the diets increased performance of the pigs by 2 to 3 pounds at 8 weeks of age. Pigs fed 20% whole whey diets for 2 weeks performed similarly as those fed 20% whole whey for 5 weeks. No differer1ces were observed between pigs fed whole whey and partially delactosed whey diets. Partially delactosed whey from two different sources produced similar pig performance. Pigs weaned at 3 and 5 weeks performed similarly and out-performed those weaned at 2 weeks. Pigs fed 20% whole whey (weaned at 2, 3, 4, or 5 weeks) outperformed pigs fed the control diet.
Keywords: Swine; Whey products; Performance; Weaned pigs